Improving the Pre-Writing Ability of Students with Intellectual Disabilities with the Sensorial Montessori Method (Classroom Action Research in Class III SLB N Simalungun, North Sumatra Province) - Astri, Yuli; Mahdi, Arisul; Ardisal, Ardisal; Nasri, Yosa Yulia (Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to describe the implementation process of the Montessori sensorial method for improving pre-writing skills of students with mild intellectual disabilities in Grade III at SLB Negeri Simalungun. The study used a collaborative Classroom Action Research (CAR) design conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The research subjects were two students with mild intellectual disabilities. Data were collected through observation, prewriting skill tests, and documentation, and were analyzed qualitatively to describe the learning process and quantitatively to identify improvements in pre-writing skills across cycles. The findings indicate a gradual and significant improvement in students’ pre-writing skills from the initial condition to the end of Cycle II, as reflected in enhanced abilities to trace lines, thicken and imitate simple patterns, and demonstrate better fine motor coordination. In addition, students showed increased active engagement, focus, and self-confidence during the learning process. The novelty of this study lies in the specific application of the Montessori sensorial method utilizing kinetic sand as a tactile sensory medium in pre-writing instruction for students with mild intellectual disabilities in a special school context, contributing both theoretically and practically to the development of adaptive learning approaches in special education.